Professores-formadores em grupos de formação continuada: possibilidades e limites da profissionalização do magistério - Budin, Clayton José [UNESP] (2014)
This research focuses on the role and the place that teachers of Basic Education have played in the continuing education of teachers. Chooses as the empirical reference Training Groups (GF) of a municipal school system in which basic education teachers play the role of trainers of their peers. The research is structured around three main axes: - the move towards professionalism of teachers; - The market for teacher training; - The place of the teacher in the professionalization of the teaching process. Had in mind, so understanding how such training proposal (GF) fits and relates to the current configuration of the teacher training market. Two procedures were essential for research: a documentary analysis and collecting data through interviews. The analyzes suggest that GF presuppose a value of teachers directly involved in working in schools in the municipal schools, since it puts them in an active position in the training of their peers, as teacher-trainers. We conclude that different actions are performed by the teachertrainer in order to take an active role in educating their peers, as this figure is suggested in a number of initiatives, so that the teacher is given a starring role and occupy a prominent place in teacher training